(untitled) (E Global Congress, 2024)
The concepts of "production costs" and "production outputs" do not mean the same thing. The second of these concepts is broader than the first, and from the point of view of society, it includes the entire volume of living and commodified labor and is equal to the value of the product. The concept of "production output" is, in most cases, associated with a certain sector of the economy (for example, production output, transaction output, etc.). Production outputs can initially be divided into two groups: tangible or actual outputs; imprecise outputs.